2003
DOI: 10.1128/aac.47.8.2606-2614.2003
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Mutant Prevention Concentration-Targeted Moxifloxacin and Levofloxacin against Streptococcus pneumoniae in an In Vitro Pharmacodynamic Model

Abstract: The differential effects of moxifloxacin and levofloxacin on the development of resistance in four Streptococcus pneumoniae isolates were examined by using an in vitro pharmacodynamic model. Therapeutic regimens (moxifloxacin: peak, 4.5 g/ml; half-life [t 1/2 ], 12 h; and levofloxacin: peak, 6 g/ml; t 1/2 , 6 h) were tested against two fluoroquinolone-susceptible isolates (strains 79 and ATCC 49619) and KD2138 and KD2139 (parC and gyrA mutants, respectively, of ATCC 49619). Mutant prevention concentration (MPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
40
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 42 publications
5
40
1
3
Order By: Relevance
“…These results further suggest that GyrA was the most crucial target for development of high-level resistance reflected in high MIC and MPC values for these three fluoroquinolones and the only target sensitive to prolonged antibiotic pressure in MPC experiments. These results are in agreement with previous findings (1,4,18,23,25,27). No clear relationship was found between the MPCs or their ratios to the MICs and the existence of gyrB, parC, or parE mutations.…”
Section: Resultssupporting
confidence: 83%
“…These results further suggest that GyrA was the most crucial target for development of high-level resistance reflected in high MIC and MPC values for these three fluoroquinolones and the only target sensitive to prolonged antibiotic pressure in MPC experiments. These results are in agreement with previous findings (1,4,18,23,25,27). No clear relationship was found between the MPCs or their ratios to the MICs and the existence of gyrB, parC, or parE mutations.…”
Section: Resultssupporting
confidence: 83%
“…Reports by Croisier et al and Allen et al showed that after levofloxacin or moxifloxacin treatment, mutants occur in vivo if there is a preexisting parC mutation since the drug concentrations fall below the MPCs of the strains. Increasing both the drug concentration and exposure to exceed the MPC may prevent mutant strains from emerging, although this strategy did not prevent the selection of secondary mutants in strains with preexisting mutations (2,5).…”
mentioning
confidence: 99%
“…However, these in vitro data should be validated in vivo by clinical trials, including full bacteriological documentation and a statistically significant number of cases due to these particular strains. Alternatively, in vitro pharmacokinetic-pharmacodynamic (PK-PD) models might help to predict gatifloxacin efficiency in these specific instances (1,5,15).…”
mentioning
confidence: 99%